A Georgian Language Island in Iran: Fereydani Georgian. Issue 3 (3rd July 2020) - Bakuradze, Lia; Beridze, Marina; Pourtskhvanidze, Zakharia
Abstract : This article describes a dialectal variant of the Georgian language in Iran, Fereydani Georgian, which has survived in Iran for about 400 years. Various relevant aspects of the history and research on Fereydani Georgian are analysed. The choice of topics and sources focuses on previously unknown or, for the English-speaking reader, inaccessible authors. Since 2009, a large part of the linguistic data has been collected in several field studies in Fereydan. They serve as sources and show a revealing perspective on the origin, preservation and existence of the Georgian language island of Fereydani in Iran.